2016
DOI: 10.1074/jbc.m115.711200
|View full text |Cite
|
Sign up to set email alerts
|

Light and pH-induced Changes in Structure and Accessibility of Transmembrane Helix B and Its Immediate Environment in Channelrhodopsin-2

Abstract: A variant of the cation channel channelrhodopsin-2 from Chlamydomonas reinhardtii (CrChR2) was selectively labeled at position Cys-79 at the end of the first cytoplasmic loop and the beginning of transmembrane helix B with the fluorescent dye fluorescein (acetamidofluorescein). We utilized (i) time-resolved fluorescence anisotropy experiments to monitor the structural dynamics at the cytoplasmic surface close to the inner gate in the dark and after illumination in the open channel state and (ii) time-resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…Double electron-electron resonance (DEER) spectroscopy showed that the intracellular end of helix 2, and of helix 6 to a lesser degree, move outward upon illumination (107–108). The results of time-resolved measurements of fluorescence anisotropy are consistent with an outward tilt of helix 2 (109). Projection maps obtained by cryo-electron microscopy suggested in addition a photoinduced movement of helix 7 (110).…”
Section: The Known Molecular Functions Of Microbial Rhodopsinssupporting
confidence: 61%
“…Double electron-electron resonance (DEER) spectroscopy showed that the intracellular end of helix 2, and of helix 6 to a lesser degree, move outward upon illumination (107–108). The results of time-resolved measurements of fluorescence anisotropy are consistent with an outward tilt of helix 2 (109). Projection maps obtained by cryo-electron microscopy suggested in addition a photoinduced movement of helix 7 (110).…”
Section: The Known Molecular Functions Of Microbial Rhodopsinssupporting
confidence: 61%
“…The recorded solution fluorescence decay traces were fitted using a multiexponential model function: It=∑inαie−t/τi,with n the total number of decay components, α i the amplitude, and τ i the fluorescence lifetime of the i th component . The analysis of the time‐resolved quenching data is based on the mean fluorescence lifetime τ m calculated by τitalicm=∑inαiτi∑inαiτiτi.…”
Section: Methodsmentioning
confidence: 99%
“…with n the total number of decay components, ␣ i the amplitude, and i the fluorescence lifetime of the ith component. 29 The analysis of the time-resolved quenching data 30,31 is based on the mean fluorescence lifetime m calculated by…”
Section: Methods For Characterization Of Mg-fitcmentioning
confidence: 99%
“…The resulting anisotropy decay curves reveal the rotational dynamics of the protein-bound probe and yield information on global and local protein dynamics as well as on the protein structure and conformational changes. 18,22,23,30 Since the probed rotational dynamics of the uorophore is affected by the motion of the protein segment to which it is covalently attached, we expect to detect nanosecond dynamics changes of helix 6 itself and of the immediate environment including structural constraints imposed by the surrounding helices (i.e., helices 7 and 8, Fig. 1A).…”
Section: Direct Observation Of Redox-dependent Structural Changes At mentioning
confidence: 99%